Modification of alkyl esters of 4-aminobenzenethiosulfonic acid by S-triazine fragment and investigation of their growth-regulative activity - Vasylyuk, Sofiya; Komarovska-Porokhnyavets, Olena; Novikov, Volodymyr; Lubenets, Vira (Lviv Politechnic Publishing House, 2018)
Досліджено ацилювання аміногрупи алкі- лових S-естерів 4-амінобензентіосульфокислоти ціанурхло- ридом. Серію естерів із триазиновим фрагментом було синтезовано та охарактеризовано елементарним аналізом, 1H- ЯМР та ІЧ-спектроскопією. Досліджено рістрегулювальну ак- тивність синтезованих сполук. Визначено певний вплив струк- тури тіосульфоестерів на їх рістрегулювальну активність.

The acylation of aminogroup of alkyl S-esters 4-aminobenzenthiosulfoacid with cyanurchloride was investigated. Series of esters with triazine fragment were synthesized and characterized by elemental analysis, 1H NMR and IR spectroscopy. The growth-regulative activity of the synthesized compounds was researched. Some appropriate effect of thiosulfoesters structure upon their growth-regulative activity was determined.
Модифікація алкілових естерів 4-амінобензентіосульфокислоти СИМ-триазиновим фрагментом та дослідження їх рістрегулювальної активності
Keywords: тіосульфокислотні похідні; тіосуль- фоестери; s-триазин; рістрегулювальна активність; thiosulfoacid derivatives; thiosulfoesters; s-triazine; growth-regulative activity